Respuesta :

Answer:

Step-by-step explanation:

Remark

You are trying to convert the base function f(x) = x^2 into the child function g(x) = -(x + 3)^2 + 5

UP

Start with the simplest part of the transformations. + 5

If you have g(x) = f(x)+5 what you have done is move the function up 5 units on your grid.

Up side Down

Next is the - sign.

f(x) = x^2

g(x) = - f(x) = - x^2

This has the affect of turning x^2 upside down. It looks like a cup opening towards the counter or down.

Left right

The last step is left / right. This is the hard one. It moves in the opposite direction that you think it should. x +3 moves the parabola left, not right. If you want it to move right, use (x - 3)

Graph

I have enclosed a graph to show you exactly what is going on. The red  line is f(x)=x^2

The blue line is g(x) = -(x + 3)^2 + 5